The temperature effect and humidity on dissolution rate of effervescent tablet - ., Ansar; Rahardjo, Budi; Noor, Zuheid; ., Rochmadi (Indonesian Journal of Pharmacy, 2006)
The aim of this study was to measure the dissolution rate constant of passion fruit effervescent tablet during storage at temperature and relative humidity variations. Sample of passion fruit effervescent tablet prepared from passion fruit granular, aspartame, polyethylene glycol, citric acid, and sodium bicarbonate.The result showed and the dissolution rate constant increased with the increasing of temperature. At elevated RH as well. The amount of dissolution rate constant was is 0.0138 with coefficient of determination (R2) was 0.7337. This calculation suggested that the proposed mathematics models might be applicable to shelf life prediction of effervescent tablet.Key words: temperature, humidity, effervescent tablet